Evaluation of learning routes in the academic performance of the mathematics area of students of the 4th grade of primary school of the I.E. Mariano Melgar, Villa María del Triunfo. Lima - Peru 2018 - Huarcaya Inga, Nilda (2018)
The scientific research we have done is basic, no causal experimental correlational study factors are two: Influence of learning routes in academic performance in the area of ??math students from the 4th grade of the IE Mariano Melgar, Villa Maria del Triunfo. Lima - Peru. 2017. The population consists of 93 students and the sample for a total of 48 students the 4th grade. The research design is transactional, correlational, causal. bivariate cross. For variable routes of learning in academic performance in the area of ??mathematics and the other will get the results of the proceedings of bimonthly evaluation that was applied to the 48 students in the sample: To collect data, a questionnaire were prepared. The instruments meet the qualities of validity and reliability. The study raises the following hypothesis: Learning Routes significantly influence academic performance in the area of ??math students in fourth grade EI No. 6019 "Mariano Melgar". The results allow us to reject the null hypothesis and accept the hypothesis investigated, as the level of significance of 5% if there is statistical evidence to say that the routes of learning influence academic performance in the area of ??mathematics students of the 4th degree, according to the correlation of Spearman's rho 0.901 is very good correlation, therefore the null hypothesis is rejected and we have: Routes Learning significantly influence academic performance in the area of ??math students in fourth grade EI No. 6019 "Mariano Melgar".